Embodiment in Cross-Linguistic Studies: The 'Eye' - Baş, Melike; Kraska-Szlenk, Iwona (BRILL, 2021)
This volume is the first book publication which focuses on conceptualization and polysemy of 'eye'. It encompasses a wide variety of languages to evidence cross linguistic similarities and differences in the semantic extensions of the eye.